The Relationship Between Students' Habit of Reading English Novels on Wattpad and Their Cross-Culture Understanding - Arni, Arni; Korompot, Chairil Anwar; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study investigates the relationship between students' habit of reading English novels on Wattpad and their Cross Culture Understanding (CCU). By using descriptive qualitative method and Focused Group Discussion (FGD) as the data collection methods and interviewing 7 English Education Students from Universitas Negeri Makassar, this study's objective is to find out whether there is or there is not a relationship between students' habit of reading English novels on Wattpad and their CCU. After the research was conducted, it is indicated that the participants agreed that reading English novels on Wattpad improved their CCU, they exhibited increased levels of empathy, respect, and tolerance, while concurrently witnessing a reduction in stereotypes, prejudice, and misjudgments. Furthermore, the research highlighted the students' beliefs with their ability to navigate cultural shocks more effectively. It can be concluded that there is a relation between students' habit of reading English novels on Wattpad and their CCU. Keywords— English novels, Wattpad, Cultures, Cross-Culture Understanding